Adaptability of high-protein barley genotypes under the conditions of the Volga-Vyatka region - I. Yu. Zaytseva; I. N. Shchennikova; L. V. Panikhina; E. V. Dyagileva (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Barley grain is unique raw material of versatile uses. More than 60% of the grain produced In the Volga-Vyatka region goes directly to fodder production purposes. One of the urgent tasks is to develop high-yielding cultivars with good grain quality, thus reducing protein deficiency in farm animal feeds and meeting the need for fodder grain that increases every year. Its successful solution requires a search for new high-yielding and high-protein source genotypes adapted to the conditions of the Volga-Vyatka region and their involvement in the breeding process.Materials and methods. Experimental work was carried out in 2018–2020 at the Federal Agricultural Research Center of the North-East named N.V. Rudnitsky, Kirov. Protein content in grain, yield, resistance to lodging, and duration of the growing season of 31 barley accessions were assessed. The barley collection was studied according to the International COMECON List of Descriptors for the Genus Hordeum L. and Methodological Guidelines. Protein content was measured using a universal rapid analyzer (INFRAMATIC 8620).Results and conclusions. Protein content had a strong correlation with Selyaninov’s hydrothermal coefficient in the interphase period from ear emergence to maturity (r = 0.85); the sum of effective temperatures during the entire growing season (r = 0.75); and precipitation in the period from seedling emergence to maturity (r = 0.67). Traits of breeding value (yield, lodging resistance, environmental plasticity, and stability) were observed in the following accessions: k-30574 (‘Filippa’, Sweden), k-30256 (‘Rodos’, Poland), ya-52 (‘Crusades’, Great Britain), k-35415 (NCL 95098, Argentina), k-30892 (‘Naran’, Russia), k-15619 (‘Polyarny 14’, Russia), ya-4 (752A, Switzerland), k-30349 (Landrace, Peru), k-5983 (Local, Afghanistan), k-3506 (Local, India), k-2929 (Local, China), k-2930 (Local, China), and k-5210 (‘Makbo’, Australia).